Electrochemical Sensors Based on Carbon Nanotubes - Saleh Ahammad, A. J. (Molecular Diversity Preservation International (MDPI), 2009)
This review focuses on recent contributions in the development of the electrochemical sensors based on carbon nanotubes (CNTs). CNTs have unique mechanical and electronic properties, combined with chemical stability, and behave electrically as a metal or semiconductor, depending on their structure. For sensing applications, CNTs have many advantages such as small size with larger surface area, excellent electron transfer promoting ability when used as electrodes modifier in electrochemical reactions, and easy protein immobilization with retention of its activity for potential biosensors. CNTs play an important role in the performance of electrochemical biosensors, immunosensors, and DNA biosensors. Various methods have been developed for the design of sensors using CNTs in recent years. Herein we summarize the applications of CNTs in the construction of electrochemical sensors and biosensors along with other nanomaterials and conducting polymers.